Deprived Muslims and Salafism: An Ethnographic Study of the Salafi Movement in Pekanbaru, Indonesia - Andri Rosadi (Religions, 2022)
This article analyses the process of reversion to Salafism in Pekanbaru, Indonesia in the context of Muslims who have returned to Islam as a solution to their sense of deprivation. This return to Islam is considered by many as an initial solution to a feeling of deprivation which often manifests itself as a form of spiritual ‘emptiness’, accompanied by anxiety, depression and a lack of direction in life. The analysis in this article is based on extensive reading of relevant literature, participatory observation, and interviews conducted during fieldwork in Pekanbaru from July 2015 to June 2016. The discussion is based on three case studies of Salafi members, detailing their reversion to Salafism and the personal and sociological reasons for their choice to return to Islam, i.e., Salafism, after a certain period of time in their lives. Findings show that those who join the Salafi movement have previously experienced relative deprivation which led to a sense of existential deprivation.